2005
DOI: 10.1091/mbc.e04-10-0935
|View full text |Cite
|
Sign up to set email alerts
|

A Minus-End–directed Kinesin with Plus-End Tracking Protein Activity Is Involved in Spindle Morphogenesis

Abstract: Diverse kinesin motor proteins are involved in spindle function; however, the mechanisms by which they are targeted to specific sites within spindles are not well understood. Here, we show that a fusion between yellow fluorescent protein (YFP) and a minus-end-directed Kinesin-14 (C-terminal family) from Arabidopsis, ATK5, localizes to mitotic spindle midzones and regions rich in growing plus-ends within phragmoplasts. Notably, in Arabidopsis interphase cells, YFP::ATK5 localizes to microtubules with a preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 58 publications
5
132
0
Order By: Relevance
“…Janson et al (2007) demonstrated that Ase1p localizes to overlapping (Ϫ) ends during interphase and overlapping plus ends in the anaphase spindle, the difference in localization being determined by molecular motors as Klp2p (a minus-end-directed motor) mediates the sliding of newly nucleated MTs along antiparallel MT bundles. In plant cells, ATK5, a plus end tracking protein molecular motor (Ambrose et al, 2005) preferentially localizes at regions of overlap between opposing interpolar MTs, suggesting an increased affinity for plus ends in an antiparallel orientation (Ambrose and Cyr, 2007). In vitro, ATK5 equally coaligns with parallel or antiparallel MTs.…”
Section: Atmap65-5 and Atmap65-1 Induce Mt Bundling Of Antiparallel Mmentioning
confidence: 99%
“…Janson et al (2007) demonstrated that Ase1p localizes to overlapping (Ϫ) ends during interphase and overlapping plus ends in the anaphase spindle, the difference in localization being determined by molecular motors as Klp2p (a minus-end-directed motor) mediates the sliding of newly nucleated MTs along antiparallel MT bundles. In plant cells, ATK5, a plus end tracking protein molecular motor (Ambrose et al, 2005) preferentially localizes at regions of overlap between opposing interpolar MTs, suggesting an increased affinity for plus ends in an antiparallel orientation (Ambrose and Cyr, 2007). In vitro, ATK5 equally coaligns with parallel or antiparallel MTs.…”
Section: Atmap65-5 and Atmap65-1 Induce Mt Bundling Of Antiparallel Mmentioning
confidence: 99%
“…In the loss-of-function mutants, atk1 and atk5, mitosis is prolonged and the spindles are somewhat broader than in the wild type [Marcus et al, 2003;Ambrose et al, 2005;Ambrose and Cyr, 2007]. In atk5, prophase spindles are longer than those of the wild type [Ambrose and Cyr, 2007], and in atk1, prophase spindles have weak or even absent bipolarity, implying that these kinesins act early in mitosis and that forming the prophase spindle involves a force balance.…”
Section: Kinesin-14 Motor Proteinsmentioning
confidence: 97%
“…The two proteins share 83% amino acid sequence identity and can crosslink both parallel and antiparallel microtubules in vitro [Ambrose et al, 2005;Ambrose and Cyr, 2007], enabling them in principle to carry out the activities ascribed to this class of kinesin in animal and fungal spindles. ATK5 tracks to the plus end of microtubules in all stages of the cell cycle, independent of the motor domain, but its motor activity is minus-end-directed [Ambrose et al, 2005]. These authors propose that the plus-end tracking targets ATK5 to the spindle midzone, from where it helps to focus the poles by crosslinking parallel microtubules and walking toward the minus ends, as has also been suggested for NCD in Drosophila [Matthies et al, 1996].…”
Section: Kinesin-14 Motor Proteinsmentioning
confidence: 99%
“…The Arabidopsis genome contains 21 C-terminal kinesins now classified as Kinesin-14, of which seven are transcriptional and up-regulated at mitosis [6,8]. The Ncd-related ATK1 and ATK5 have been shown to move in the minusend direction of MTs and to associate with spindle MTs where they are required for focusing the MTs at the poles, which is similar to Ncd activity ( Figure 2) [33][34][35][36]. Compared with other organisms, the Kinesin-14 group is relatively large.…”
Section: M-phase-specific Kinesins Related To Animal Kinesinsmentioning
confidence: 99%
“…Spindle poles are broad in plant cells and poles are focused at the centrosomes in animal cells. Antagonistic forces of Kinesin-14, such as Ncd [81] and Arabidopsis ATK1 [35] and Kinesin-5, such as DmKLP61F [81], HsEg5 or AtTKRP125 establish spindle bipolarity, whereas Kinesin-14 members Ncd, ATK1 and ATK5 focus on the minus-ends of the spindle MTs [32][33][34][35][36]. Furthermore, members of the depolymerizing Kinesin-13 family (DmKLP10A and HsKIF2A) function in mitotic spindle assembly and maintenance [62].…”
Section: M-phase-specific Kinesins Related To Animal Kinesinsmentioning
confidence: 99%